2016
DOI: 10.1021/acs.orglett.6b01186
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Catalyzed Enantioselective Hydrogenation of 1,8-Naphthyridine Derivatives

Abstract: The first asymmetric hydrogenation of 2,7-disubstituted 1,8-naphthyridines catalyzed by chiral cationic ruthenium diamine complexes has been developed. A wide range of 1,8-naphthyridine derivatives were effectively hydrogenated to give 1,2,3,4-tetrahydro-1,8-naphthyridines with up to 99% ee and full conversions. The method provides a practical and facile approach to the preparation of valuable chiral heterocyclic building blocks and useful motifs for a new kind of P,N-ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…In particular, the AH of heteroaromatic compounds has recently been an important topic in asymmetric catalysis . A number of N‐containing heteroaromatic substrates, including quinolines, quinoxalines,– isoquinolines, indoles, pyrroles,, pyridines, indolizidines, pyrimidines, phenanthrolines,, and naphthyridines,, have been successfully hydrogenated with excellent enantioselectivity. Expectedly, direct asymmetric reduction of the readily available aromatic bisheterocycles (e.g., 2,2′‐bisquinolines) is undoubtedly the most convenient strategy for obtaining chiral rigid endocyclic diamines.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the AH of heteroaromatic compounds has recently been an important topic in asymmetric catalysis . A number of N‐containing heteroaromatic substrates, including quinolines, quinoxalines,– isoquinolines, indoles, pyrroles,, pyridines, indolizidines, pyrimidines, phenanthrolines,, and naphthyridines,, have been successfully hydrogenated with excellent enantioselectivity. Expectedly, direct asymmetric reduction of the readily available aromatic bisheterocycles (e.g., 2,2′‐bisquinolines) is undoubtedly the most convenient strategy for obtaining chiral rigid endocyclic diamines.…”
Section: Methodsmentioning
confidence: 99%
“…Most recently, we found that the Ru complexes of chiral vicinal diamines, which are often used as catalysts for asymmetric transfer hydrogenation, are highly efficient in the AH of N‐containing heteroaromatic compounds and give excellent enantioselectivity ,. For example, a wide range of quinolines, including 2‐aryl quinolines, could be effectively hydrogenated with high reactivity and enantioselectivity .…”
Section: Methodsmentioning
confidence: 99%
“…[44] Fan et al have also explored analogous complexes for the enantioselective hydrogenation of naphthalene derivatives in the presence of H 2 gas. [45][46] Notably,t hese and plenty of other transfer hydrogenation/hydrogenation reactions catalysed by (arene)Ru-en-based complexes target mainly C=Oo r C=Nb onds. [38][39][40][41][42][44][45][46] However,ata ne levated temperature (60-100 8C) using high-pressure H 2 gas (10-60 bar), the hydrogenation of C=Cb onds (aromatic and others) catalysedb yR uc omplexes was also successful.…”
Section: Introductionmentioning
confidence: 99%
“…[45][46] Notably,t hese and plenty of other transfer hydrogenation/hydrogenation reactions catalysed by (arene)Ru-en-based complexes target mainly C=Oo r C=Nb onds. [38][39][40][41][42][44][45][46] However,ata ne levated temperature (60-100 8C) using high-pressure H 2 gas (10-60 bar), the hydrogenation of C=Cb onds (aromatic and others) catalysedb yR uc omplexes was also successful. [47][48][49][50] The striking work of Finke et al established that at ah igh temperature (110 8Ca nd 60 atm H 2 ), the catalytic reaction performed using ruthenium metal complexes, actually generated traces of Ru 0 nanoparticles in situ as the active catalytic species for the hydrogenation of benzene.…”
Section: Introductionmentioning
confidence: 99%
“…8 Among these methods, the hydrogenation of 1,8-naphthyridines provides a clean and straightforward approach for the synthesis of 1,2,3,4-tetrahydro-1,8-naphthyridines. In 2015, Fan and coworkers reported the first highly regio-and enantioselective hydrogenation of 1,5-naphthyridines catalyzed by a chiral Ru complex. 10 Despite these advances, metal-free hydrogenation of 1,8-naphthyridines has rarely been reported. 10 Despite these advances, metal-free hydrogenation of 1,8-naphthyridines has rarely been reported.…”
mentioning
confidence: 99%